A Comprehensive View on the Host Factors and Viral Proteins Associated With Porcine Epidemic Diarrhea Virus Infection - Hu, Yi; Xie, Xiaohong; Yang, Lingchen; Wang, Aibing (Frontiers in Microbiology, 2021)
Porcine epidemic diarrhea virus (PEDV), a coronavirus pathogen of the pig intestinal tract, can cause fatal watery diarrhea in piglets, thereby causing huge economic losses to swine industries around the world. The pathogenesis of PEDV has intensively been studied; however, the viral proteins of PEDV and the host factors in target cells, as well as their interactions, which are the foundation of the molecular mechanisms of viral infection, remain to be summarized and updated. PEDV has multiple important structural and functional proteins, which play various roles in the process of virus infection. Among them, the S and N proteins play vital roles in biological processes related to PEDV survival via interacting with the host cell proteins. Meanwhile, a number of host factors including receptors are required for the infection of PEDV via interacting with the viral proteins, thereby affecting the reproduction of PEDV and contributing to its life cycle. In this review, we provide an updated understanding of viral proteins and host factors, as well as their interactions in terms of PEDV infection. Additionally, the effects of cellular factors, events, and signaling pathways on PEDV infection are also discussed. Thus, these comprehensive and profound insights should facilitate for the further investigations, control, and prevention of PEDV infection.